Substitution of Desiccated Coconut on The Physicochemical and Organoleptics of Crispy Cookies - Sari, Maria Mega; Priyono, Suko; Saputri, Nur Endah; Rahmadian, Yudi (Media Publikasi Cendekia Indonesia, 2024)
Research on coconut flour and desiccated coconut substitution cookies has been conducted by several researchers, but variations of desiccated coconut crispy cookies have not been widely developed. The nutritional content of desiccated coconut can be used as a source of fiber when substituted in crispy cookies products. The purpose of this study was to determine the effect of desiccated coconut substitution in making crispy cookies on physicochemical and organoleptic characteristics, and obtain the best desiccated coconut substitution. This study used a Complete Randomized Design (RAL) with one factor, namely the ratio of the percentage of desiccated coconut and wheat flour with 6 treatment levels (0:100), (25:75), (50:50), (75:25), (85:15), and (100:0) with 3 repeats. The data obtained were analyzed using the ANOVA test (α=5%). If the effect is significant (Sig < 0.05), then proceed with the Honest Real Difference Test (BNJ) with a test level of 5%. Analysis of sensory characteristics data using the Kruskal Wallis test. The best treatment is tested using an effectiveness index test. This study obtained the best sensory and physicochemical characteristics of desiccated coconut crispy cookies in treatment (25%: 75%). The physicochemical characteristics produced are crude fiber content of 2.73%, fat content of 30.43%, ash content of 1.52%, water content of 16.86%, carbohydrate content of 51.11%, and protein content of 0.08%. The resulting sensory characteristics are taste 4.36 (prefer), aroma 4.13 (prefer), color 3.97 (like), and texture 4.26 (prefer).